ANALISIS PENGARUH HUMAN RELATION, DISIPLIN KERJA, DAN FAKTOR LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI DSOCIETY CABANG MEDAN SEBAGAI STARTUP - Prayogi, Mugi Anggara; Dirbawanto, Nana Dyki (Transpublika Publisher, 2023)
The objective of this study is to examine the impact of Human Relations, Work Discipline, and Work Environment on Employee Performance at the Medan Branch of DSociety Start Up Company. The research adopts a quantitative approach and focuses on the employees of the DSociety Medan Branch Start Up Company as the population. A sample of 31 respondents was selected using purposive sampling. Data was collected through a questionnaire method, utilizing a Likert scale for measurement. The analytical techniques employed in this study include the classical assumption test, multiple linear regression analysis, multiple correlation analysis, and hypothesis testing using SPSS. The findings of this study reveal that Human Relations, Work Discipline, and Work Environment significantly influence Employee Performance. The Adjusted R Square value of 0.375 indicates that these variables collectively account for 37.5% of the variance in Employee Performance. Therefore, it can be concluded that there is a direct correlation between Human Relations, Work Discipline, Work Environment, and Employee Performance. The remaining variance in Employee Performance is attributed to other unexamined variables.